The economic value of low-energy housing. (2nd January 2016) - Wu, Hao; Crawford, Robert H.; Warren-Myers, Georgia; Dave, Malay; Noguchi, Masa
Abstract: This paper explores a new perspective towards understanding barriers to ascertaining the economic value of low-energy housing. It examines why the economic value of low-energy housing is less transparent in active markets; this is investigated from the valuation principle perspectives of embodied energy and operational energy in residential dwellings. The focus is placed on the composition of energy consumption associated with the housing product life cycle. Low operational energy of a dwelling is linked to consumer preference by the inter-temporal value estimate of expected benefits. However, "low" embodied energy housing is an ecological construct and does not appear to be directly linked to short-term market value or an expected (intuitive) economic motive. This "gap/disconnect", alongside some practical "barriers" in the market economy, has created a challenge in deriving the economic value of low-energy housing. The barrier to economic value of low-energy housing is methodological and by adopting a life cycle approach to assessing and measuring energy in a house that incorporates embodied energy and operational energy, greater clarity can be achieved which may lead to a better informed market, enhancing transparency and allowing consumer choice to direct and value the broader benefits of low-energy housing.